Outer membrane vesicles as a versatile nanoplatform for advanced vaccine development and immunotherapy - Zhang, Jiawen; Zhi, Yuhang; Lu, Yu; Ma, Fang (Frontiers in Immunology, 2026)
Bacterial outer membrane vesicles (OMVs) are nano-sized, lipid-bilayer vesicles naturally released by Gram-negative bacteria. These vesicles are enriched with diverse biomolecules, including lipids, proteins, and nucleic acids, enabling them to mediate critical biological processes. Emerging evidence highlights their pivotal roles in bacterial physiology, intercellular communication, and environmental adaptation, alongside their promising therapeutic potential. This review focuses on recent advances in OMV biogenesis, composition, function and applications. By integrating current knowledge, we aim to inspire novel insights into the molecular mechanisms underlying OMV functions and facilitate their translational development in medicine. Ultimately, this work serves as a comprehensive reference to accelerate future research and clinical utilization of this versatile platform.